Multiple stressor effects of a heatwave and a herbicide on zooplankton communities: Implications of global climate change - Roth, Sabrina K.; Polazzo, Francesco; García-Astillero, Ariadna; Cherta, Laura; Sobek, Anna; Rico, Andreu (Frontiers in Environmental Science, 2022)
Aquatic ecosystems are exposed to pesticides through various pathways such as spray-drift, agricultural runoff, and chemical spills. Understanding the impact of pesticides on freshwater ecosystems requires not only understanding how pesticides affect aquatic organisms but also knowledge of their interactions with other stressors, such as those related to global climate change. Heatwaves are extended periods of temperature increase relative to the climatological mean. They are increasing in frequency and magnitude and pose an emerging threat to shallow freshwater ecosystems. In this study, we evaluated the single and combined effects of the herbicide terbuthylazine and a simulated heatwave on freshwater zooplankton communities using indoor microcosms. Terbuthylazine was applied at an environmentally relevant concentration (15 µg/L). The heatwave consisted of an increase of 6°C above the control temperature for a period of 7 days. When applied individually, the heatwave increased the total abundance of zooplankton by 3 times. The terbuthylazine exposure led to an indirect effect on the zooplankton community structure, reducing the relative abundance of some taxa. The combination of the heatwave and terbuthylazine had no significant impact on the zooplankton community, indicating additive effects dominated by the herbicide. The interaction between the two stressors increased chlorophyll-a concentrations and apparently changed the structure of the phytoplankton community, which may have benefitted cyanobacteria over green algae. Overall, this study shows that understanding the effects of chemical and non-chemical stressors on aquatic communities remains a challenging task. Further studies should be conducted to improve our mechanistic understanding of multiple stressor interactions at different levels of biological organisation.